2006
DOI: 10.1016/j.jcrs.2006.07.025
|View full text |Cite
|
Sign up to set email alerts
|

Cumulative neodymium:YAG laser rates after bag-in-the-lens and lens-in-the-bag intraocular lens implantation

Abstract: The cumulative Nd:YAG laser rate after bag-in-the-lens implantation was zero. A zero rate has not been reported with lens-in-the-bag implantation of an IOL of the same biomaterial or of other biomaterials, as published in the literature. Thus, it can be concluded that the bag-in-the-lens implantation technique has 100% effectiveness against posterior capsule opacification.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
38
0
4

Year Published

2007
2007
2019
2019

Publication Types

Select...
5
4

Relationship

4
5

Authors

Journals

citations
Cited by 54 publications
(42 citation statements)
references
References 20 publications
0
38
0
4
Order By: Relevance
“…4,5 These results exceed the best results obtained with any other IOL implanted in the bag. 6 We report the results of implantation of this new IOL design using a modified technique in pediatric eyes.…”
mentioning
confidence: 70%
“…4,5 These results exceed the best results obtained with any other IOL implanted in the bag. 6 We report the results of implantation of this new IOL design using a modified technique in pediatric eyes.…”
mentioning
confidence: 70%
“…23 In the present study, we found no increased risk for severe adverse events. After the 1-year follow-up of the first 60 patients, there were no cases of visual axis reproliferation 6 and no signs of inflammatory reaction at the level of the anterior hyaloid; this was a concern in a previous study by Praveen et al 24 Interim visual axis reproliferation results after BIL IOL implantation in adults 25 and in children [12][13][14][15][16][17][18][19][20][21][22][23][24][25][26] have been published. This more exhaustive follow-up study confirms the previously published data.…”
Section: Discussionmentioning
confidence: 99%
“…No cases of PCO were detected over the course of the follow-up. The BIL design seals lens epithelial cells away from the anterior vitreous and is the only lens with a 0% rate of PCO reported here and elsewhere [8]. Although the creation of a PPCCC may similarly open the chamber, the BIL technique stresses the maintenance of an intact anterior hyaloid and forms a tight seal which reestablishes the barrier of the posterior capsule.…”
Section: Discussionmentioning
confidence: 75%
“…1). In addition to completely preventing PCO, this lens position is very stable and highly resistant to rotation and decentration [8,9,10]. …”
Section: Introductionmentioning
confidence: 99%